Network Access and Market Power - Ekaterina Orlova; Franz Hubert (ZBW - Deutsche Zentralbibliothek für Wirtschaftswissenschaften, Leibniz-Informationszentrum Wirtschaft, 2014)
We study the impact of the liberalization of EU natural gas markets on the balance of power between `local champions', customers, and outside producers. We distinguish between two steps of the reform: 1. opening access to transit pipes and 2. opening access to distribution systems, hence customers. Using the Shapley value as a power index, we find a modest and rather heterogeneous impact from the first step. The impact of the second step is much larger and yields a clear pattern: all local champions lose, while all customers and all outside players gain. As one third of the losses of champions within EU leaks to players abroad, current reforms might enhance the dominance of already powerful outside producers. This effect, however, completely vanishes, when network power is assessed with the nucleolus.
Keywords: L51; L95; C71; 330